Adaptive Speed Control of Induction Motor Drive With Inaccurate Model - Talla, Jakub; Viet Quoc Leu; Smidl, Vaclav; Peroutka, Zdenek (IEEE transactions on industrial electronics (1982), 2018)
An adaptive controller for the speed control of induction motor (IM) drives with inaccurate models is designed in this paper. Specifically, we assume that every equation in the state-space model of the drive is subject to slowly varying error. The proposed controller is composed of an adaptive feedforward control term, which compensates for the nonlinear and uncertain factors, and a feedback control term, which guarantees the system stability. The proposed scheme is not only simple and easy to implement, but also it guarantees a precise and fast speed tracking. Stability of the proposed speed controller is confirmed using the Lyapunov theorem and a related lemma. The designed control algorithm is compared to a controller based on nonadaptive feedback linearization control (FLC), conventional field oriented control (FOC), and adaptive backstepping sliding mode control (ABSMC). Experiments on a developed IM drive prototype of rated power of 4 kW confirm good control performance [better robustness, smaller mean square, and maximum absolute errors (MAEs)] compared to the competitors, especially in the case of severe parameter mismatch between the real drive and model used for controller design.